: AN EXPERIMENTAL STUDY IN INDONESIAN ISLAMIC BOARDING SCHOOLS - Kinnatul ‘Ashriyyah, Annisa Ainurrohmah, Muhammad A'inul Haq, Ulya Mahfudhotun Najwa, (Jurnal Pendidikan Bahasa Arab, 2025)
This study explores how memory strategies can improve Arabic speaking skills among students at Indonesian Islamic institutes. A quasi experimental method with a one-group pretest-posttest design was used, involving 81 students in an eight-week program that integrated various memory techniques like vocabulary recall, repetition, and association into speaking practice. Data were collected through speaking tests given before (pretest) and after (posttest) the intervention, alongside observations and questionnaires. Statistical analysis with a paired-sample t-test showed a significant improvement in speaking skills, with average scores rising from 62.50 in the pretest to 75.30 in the posttest. A high correlation coefficient of 0.988 and a significance value of 0.000 led to the rejection of the null hypothesis. These results indicate that using memory strategies effectively enhances vocabulary retention and speaking fluency in Arabic. The discussion underlines the positive connection between these strategies and improved oral skills, shedding light on the cognitive processes involved. The study concludes that incorporating memory strategies into Arabic language teaching in Islamic boarding schools not only boosts speaking skills but also builds students’ self-confidence. It recommends that teachers implement various memory-enhancing techniques to create a more effective and engaging learning environment.